Zigbee Based Temperature Monitoring and Controlling in Matlab - Chaman, Shilpa (Asian Journal of Electrical Sciences, 2013)
Efficient design and implementation of wireless sensor network has become an emerging area of research in recent years, due to vast potential of sensor network enables application that connect the physical world to the virtual world. By networking large numbers of Zigbee sensor nodes, it is possible to obtain data about physical phenomena that was difficult or impossible to obtain in conventional ways. In this paper a wireless temperature sensing and controlling system for real time dynamics has been proposed. Variation in the temperature is recorded in the GUI window and proper controlling action is taken accordingly. An 8-bit Atmega16 [1] microcontroller has been used to interface the temperature sensor using the IEEE 802.15.4 standard, Zigbee protocol. Zigbee has the characteristics of low power consumption, low cost and self organizing features.